Learning and Territory. Design as a leverage for sustainable development in local communities - Pignalberi, Claudio (Form@re - Open Journal per la formazione in rete, 2020)
The paper focuses on the importance of training design for the development of the territory by outlining the functions, learning contents and skills of the subject for the definition and cultivation of sustainable practices for well-being and active citizenship. The paper, therefore, invites the reader to reflect on the theme of training, identifies educational practices and development prospects and then presents the results of a training project carried out in a small lazial village. It is precisely from the small local realities that it is possible to open the space for a design aimed at training citizens who are protagonists able to provide their contribution to responsibly inhabit the territory, in the acquired awareness of the close interdependence that unites person and community, between local and global. Apprendimento e Territorio. La progettazione come leva per lo sviluppo sostenibile nelle comunità locali Il contributo si concentra sull’importanza della progettazione formativa per lo sviluppo del territorio delineando le funzioni, i contenuti di apprendimento e le skills del soggetto per la definizione e coltivazione di pratiche sostenibili per il benessere e la cittadinanza attiva. Il contributo, pertanto, invita il lettore ad una riflessione sul tema della formatività, individua le pratiche educative e le prospettive di sviluppo per poi presentare i risultati di un progetto formativo realizzato in un piccolo borgo laziale. È proprio dalle piccole realtà locali che è possibile aprire lo spazio per una progettazione mirante a formare cittadini protagonisti in grado di fornire il proprio contributo per abitare responsabilmente il territorio, nell’acquisita consapevolezza della stretta interdipendenza che unisce persona e comunità, tra locale e globale.